(untitled) (Journal of Pharma Insights and Research, 2025)
Polyalthia longifolia (Annonaceae) is a valuable medicinal plant widely distributed across South and Southeast Asia. The plant exhibits distinct morphological characteristics, including a tall, evergreen habit with a pyramidal crown and pendulous branches. Various parts of P. longifolia contain bioactive compounds such as alkaloids, flavonoids, terpenoids, and phenolic compounds. Traditional medicine systems have utilized P. longifolia for treating fever, skin diseases, diabetes, hypertension, and helminthiasis. Recent pharmacological studies demonstrate its potential in managing various health conditions. The leaves exhibit anti-ulcer, antiplasmodial, and anti-inflammatory properties, while the bark shows promising results in wound healing and antimicrobial applications. The main therapeutic effects include antihyperglycemic activity through α-amylase and α-glucosidase inhibition, anticancer properties against prostate cancer cells, and immunomodulatory effects on B and T lymphocytes. The plant also demonstrates antiviral activity against paramyxoviruses and antileishmanial properties through DNA topoisomerase inhibition. Modern scientific investigations validate many traditional uses while revealing new therapeutic applications. Various studies related to pharmacological activities of P. longifolia proves it as a valuable source for developing novel therapeutic agents